A Positive Feed Forward Loop between Wnt/β-Catenin and NOX4 Promotes Silicon Dioxide-Induced Epithelial-Mesenchymal Transition of Lung Epithelial Cells. (9th December 2020) - Ma, Jia; Cai, Qian; Yang, Dandan; Yang, Jiali; Xue, Jing; Yu, Miao; Liu, Yingxue; Ma, Fucheng; Li, Feng; Liu, Xiaoming
Abstract : Silicosis is a chronic fibrotic lung disease caused by the accumulation of silica dust in the distal lung. Canonical Wnt signaling and NADPH oxidase 4 (NOX4) have been demonstrated to play a crucial role in the pathogenesis of pulmonary fibrosis including silicosis. However, the underlying mechanisms of crosstalk between these two signalings are not fully understood. In the present study, we aimed to explore the interaction of Wnt/ β -catenin and NOX4 of human epithelial cells in response to an exposure of silica dust. Results demonstrated an elevated expression of key components of Wnt/ β -catenin signaling and NOX4 in the lungs of silicon dioxide- (SiO2 -) induced silicosis mice. Furthermore, the activated Wnt/ β -catenin and NOX4 signaling are accompanied by an inhibition of cell proliferation, an increase of ROS production and cell apoptosis, and an upregulation of profibrogenic factors in BEAS-2B human lung epithelial cells exposed to SiO2 . A mechanistic study further demonstrated that the Wnt3a-mediated activation of canonical Wnt signaling could augment the SiO2 -induced NOX4 expression and reactive oxygen species (ROS) production but reduced glutathione (GSH), while Wnt inhibitor DKK1 exhibited an opposite effect to Wnt3a. Vice versa, an overexpression of NOX4 further activated SiO2 -induced Wnt/ β -catenin signaling and NFE2-related factor 2 (Nrf2) antioxidant response along with a reduction of GSH, whereas the shRNA-mediated knockdown of NOX4 showed an opposite effect to NOX4 overexpression. These results imply a positive feed forward loop between Wnt/ β -catenin and NOX4 signaling that may promote epithelial-mesenchymal transition (EMT) of lung epithelial cells in response to an exposure of silica dust, which may thus provide an insight into the profibrogenic role of Wnt/ β -catenin and NOX4 crosstalk in lung epithelial cell injury and pathogenesis of silicosis.